Self-organized dynamic resource allocation using fraction frequency reuse scheme in long term evolution networks. (November 2015) - Mohamed, Ahmed S.; Abd-Elnaby, Mohammed; El-Dolil, Sami A.
Abstract : Graphical abstract: Highlights: We proposed a self-organized dynamic resource allocation (SORA) scheme using FFR. SORA-FFR scheme tracks the variation of UEs distribution through the LTE network. SORA-FFR scheme dynamically allocates optimal resources to inner and outer regions. SORA-FFR scheme improved throughput of CEUs and fairness performance. Abstract: Inter-Cell Interference (ICI) from neighboring cells is the major challenge that degrades the performance of Orthogonal Frequency Division Multiple Access (OFDMA) cellular mobile systems, particularly for cell edge users. An efficient technique to mitigate ICI is the interference coordination. The most commonly ICI Coordination (ICIC) technique is the Fractional Frequency Reuse (FFR), which effectively mitigates ICI by applying different reuse factors to Users' Equipments (UEs) situated in different regions in each cell. This paper presents a novel Self-Organized FFR Resource Allocation (SORA) scheme that automatically selects the optimal RA to inner and outer regions of the cell, based on coordination between neighboring evolved NodeBs (eNBs), through a message passing approach over Long Term Evolution (LTE)-X2 interfaces. The performance of the proposed scheme is evaluated using MATLAB and compared with different combinations of RA as well as with frequency reuse-1 and reuse-3 schemes. Simulation results show that the proposed scheme improves the cell-edge performance and achieves high degree of fairness among UEs compared to reference RA schemes.